2011
DOI: 10.1186/1472-6750-11-18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a recombinant gene expression on ColE1-like plasmid segregation in Escherichia coli

Abstract: BackgroundSegregation of expression plasmids leads to loss of recombinant DNA from transformed bacterial cells due to the irregular distribution of plasmids between the daughter cells during cell division. Under non-selective conditions this segregational instability results in a heterogeneous population of cells, where the non-productive plasmid-free cells overgrow the plasmid-bearing cells thus decreasing the yield of recombinant protein. Amongst the factors affecting segregational plasmid instability are: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 50 publications
(70 reference statements)
1
29
0
Order By: Relevance
“…This presents a clear evidence that inactivation of transcription has a strong stabilizing effect on the plasmid against segregation. This finding is supported also by a recent study where the role of transcription on plasmid segregation was investigated in a chemostat culture (18).…”
Section: Relationship Between Hifnγ Gene Transcription and Plasmid Sesupporting
confidence: 77%
See 2 more Smart Citations
“…This presents a clear evidence that inactivation of transcription has a strong stabilizing effect on the plasmid against segregation. This finding is supported also by a recent study where the role of transcription on plasmid segregation was investigated in a chemostat culture (18).…”
Section: Relationship Between Hifnγ Gene Transcription and Plasmid Sesupporting
confidence: 77%
“…1. The plasmid pΔP 1 IFNγC was derived from the expression plasmid pIFNγC by removing the EcoRI/HindIII fragment (bearing both P 1 promoter and the SD sequence), blunting and ligation (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a relationship between gene expression and plasmid segregation was shown for ColE1-like plasmids in E. coli (37): it was argued that transcription and translation interfere with plasmid replication, leading to low copy numbers and finally to plasmid loss. We did not detect complete plasmid loss, and a highly related plasmid has been described as being stably maintained in B. megaterium, even without selective pressure (38). We eventually concluded that the transcriptional and translational machinery slows down the distribution of plasmids in B. megaterium.…”
Section: Discussionmentioning
confidence: 71%
“…Conventionally this is achieved through cultivationbased methods in which diluted bacterial suspensions are spread on media with and without selection for plasmid-bearing cells or by replicating bacterial colonies (e.g., 50 or 100) from nonselective plates onto plasmid-selective and nonselective agar plates (4,5,(12)(13)(14)(15)(16)(17). However, this is labor-intensive, requires colony growth on agar, and has a built-in lag period of one or more days prior to knowing the results.…”
mentioning
confidence: 99%